Buyer-led environmental supplier development: Can suppliers really help it? - Saghiri, Soroosh; Mirzabeiki, Vahid (Elsevier, 2020)
The importance of supplier development programs to enhance supply chain environmental capabilities has often been posited. However, the literature is limited in identifying and explaining the factors that may influence or mediate the effectiveness of such programs. This paper examines the role of environmental supplier development programs led by the buying organization on supplier environmental practices, while testing the mediating effects of the supplier in the forms of resource allocation and collaboration with the buyer. The relationships are tested based on survey data from 267 supplier organizations in the UK using Partial Least Squares (PLS). The results indicate that supplier development in the form of setting requirements and audits has a wide, positive impact on all supplier environmental activities, while environmental supplier development in the form of direct projects only affects supplier environmental activities in logistics and transport. The results for the mediation effects tested are varied: while supplier collaboration is important to enhance the supplier logistics and transport activities, supplier resource allocation proves to be mediating the impact of environmental supplier development on the supplier energy efficiency and logistics and transport activities. The research sheds new light on the effectiveness of supplier development and environmental programs. The findings indicate that buying organizations should make explicit reference to the way they define supplier collaboration and resource allocation for their environmental plans and environmental supplier development programs to be effective
Keywords: Buyer-supplier collaboration; Logistics Resource allocation; Energy efficiency; Environmental supplier development